The effect of α2-δ and other accessory subunits on expression and properties of the calcium channel α1G - Dolphin, A C (Blackwell Science Inc, 1999)
1. The effect has been examined of the accessory α2-δ and β subunits on the properties of α1G currents expressed in monkey COS-7 cells and Xenopus oocytes. 2. In immunocytochemical experiments, the co-expression of α2-δ increased plasma membrane localization of expressed α1G and conversely, the heterologous expression of α1G increased immunostaining for endogenous α2-δ, suggesting an interaction between the two subunits. 3. Heterologous expression of α2-δ together with α1G in COS-7 cells increased the amplitude of expressed α1G currents by about 2-fold. This finding was confirmed in the Xenopus oocyte expression system. The truncated δ construct did not increase α1G current amplitude, or increase its plasma membrane expression. This indicates that it is the exofacial α2 domain that is involved in the enhancement by α2-δ. 4. β1b also produced an increase of functional expression of α1G, either in the absence or the presence of heterologously expressed α2-δ, whereas the other β subunits had much smaller effects. 5. None of the accessory subunits had any marked influence on the voltage dependence or kinetics of the expressed α1G currents. These results therefore suggest that α2-δ and β1b interact with α1G to increase trafficking of, or stabilize, functional α1G channels expressed at the plasma membrane.